Berat badan lahir lebih dari 4000 gram merupakan faktor risiko kejadian mikropenis pada bayi baru lahir di Denpasar tahun 2019 - I Gusti Bagus Dharma Prakasa Musti; Gede Wirya Kusuma Duarsa; Tjok Gde Mahadewa; Gede Wirata (DiscoverSys Inc., 2019)
Background: Standard values related to age for penis size can help for early diagnosis and treatment of potential diseases. Rapid changes in growth and interindividual differences can occur during infancy and puberty. Therefore, micropenis data during newborns are beneficial for clinical evaluation and prognosis.Aim: This study aims to find out whether birth weight > 4000 grams and testis size <0.52 cm are risk factors for micropenis prevalence in newborns.Methods: This study used a descriptive-analytical cohort study involving 85 research subjects, namely healthy newborn boys who did not experience hypospadias, severe chordae, ambiguous penises. Respondents contributed to physical examinations and investigations following the standard procedure in the analysis of the weight, gestational age, and size of the testis. The study also evaluated the risk factors for micropenis in the form of a history of maternal hormonal birth control.Results: The micropenis was categorised to be <1.8 cm, which was obtained from <2.5 SD mean where the size of penis length in this study was achieved with a mean of 2.08 cm. The results of the multi-variate test showed that birth weight> 4000 grams was the most dominant risk factor causing micropenis. The positive B value with a value of 5.13, which means birth weight> 4000 grams has a positive relationship with the incidence of micropenis. The newborn weight was obtained about p = 0,000 (95%CI: 11,29-2558,17) with OR 170 which mean that there was an effect of birth weight on the incidence of micropenis where birth weight> 4000 grams had a chance of micropenis by 170 times.Conclusion: Weight> 4000 grams became the most dominant risk factor for micropenis having probabilities for a micropenis approximately 170 times.